Reinterpreting the Vitruvian model in contemporary architectural education: integrating empirical insights from five schools of architecture - Selim, Haitham Sadek; Mayhoub, Mohammed Salah; Abuzaid, Abdullah (Frontiers in Education, 2025)
Architectural education requires integrated methodologies. There is also significant variation in definitions, pedagogical ideologies, and curricular practices across institutions, indicating the need for a common framework that enables architecture schools to respond effectively to contemporary challenges. This study explores the possibility of reviving the Vitruvian model as a unified, adaptable, and evolving model for architectural pedagogy. A structured questionnaire was distributed to faculty members at five international architecture schools, representing the American, British, French, German, and Egyptian systems. In total, 136 valid responses were obtained and analyzed. Statistical analysis, including chi-square tests, revealed no significant correlation between academic status, years of experience, or interpretive preferences and the pedagogical model, suggesting that perspectives on architectural education transcend national boundaries. The findings highlight a contemporary reinterpretation of Vitruvian principles, emphasizing sustainability, interdisciplinary collaboration, and human-centered design as key elements of the architectural curriculum. This study clarifies how the Vitruvian triad can be reinterpreted to advance sustainability, interdisciplinarity, and human-centredness in architectural education, and translates these insights into studio-based practices that more closely align with professional practice.